Prevalence Of Orthodontıc Malocclusıons On School Chıldren In Konya: An Epıdemıologıc Study - Faruk Ayhan Başçiftçi; Abdullah Demir; Zafer Sarı; Tancan Uysal (Galenos Yayinevi, 2002)
Epidemiology is the study of the factors that govern the frequency and distribution of disease or physiologic states in a community. Its focus is on the total population rather than the in the individual, and its purpose is disease classification and prevention. The aim of this study was to investigate the prevalence of orthodontic malocclusions in school children and to examine the statistical sex differences between these anomalies. In this study 965 subjects ages changes between 6 to 19 years are examined. The prevalence of orthodontic malocclusions including Angle classification, posterior cross-bite, anterior cross bite, dental crowding, increased overjet, open bite, and deep bite were examined. The preparation of malocclusion tables and the subsequent statistical analysis (chi-square) of the frequencies were performed by means of computer programs (SPSS for Windows Release 10.0). Of all children 81% have orthodontic malocclusion and 76.4 % showed Class I dental malocclusion. For open bite the sex difference was significant. In regard to occlusal anomalies, the sagittal deviations showed no significant sex difference. As a result: because of the high proportion of orthodontic malocclusion, we must do more preventive and interceptive orthodontic treatments to our all patients.